Gender and School Ownership on Mathematics Anxiety of Junior Secondary School Students in Mezam Division - Monique Abongkeyung Newen; Nfor Julius Cheny (International Journal on Integrated Education, 2021)
The purpose of the study was to investigate the influence of gender and school ownership on Mathematics anxiety of junior secondary school students in North West and South West regions of Cameroon. Three research questions were formulated and three null hypotheses stated to guide the study. Relevant literature materials to the study were reviewed. The subjects were composed through a multistage random sampling technique. The subjects were form three students and they were 960 in number. The instrument used for the collection of data was Mathematics Anxiety Rating Scale (MARS). The instrument was face validated by five experts, two in Mathematics education, one in Psychology, one in Measurement and Evaluation and one in Curriculum studies. The two instruments were trial tested. The internal consistency of MARS was computed as 0.815 using Cronbach alpha (α). The data obtained were analyzed using Means and Standard Deviation for answering research questions while the hypotheses were tested at 0.05 level of significance using ANOVA and t-test. The results of the study revealed that gender did not have any significant influence on students’ Mathematics anxiety. Also school ownership did not have any significant influence on students’ Mathematics anxiety. Results again showed that there was no significant interaction of gender and school ownership on students’ Mathematics anxiety. Following the discussions of these findings the educational implications were pointed out and recommendations made. Mathematics teachers are encouraged to employ teaching practices that do not promote gender bias and must consider giving the same treatment and Mathematics tasks to both males and females. This can be done through organizing seminars, workshops and conferences sponsored by the government or professional associations. In view of the fact that gender has no significant influence on students’ Mathematics anxiety, more women can be encouraged into Mathematics, Science and Information technology fields.